Intertextual Dialogue between Nizar Qabbani's Poetry “تَرصيعٌ بِالذَّهَبِ عَلَى سَيْفٍ دِمَشْقِيٍّ” and Zoulfa Katouh's Novel As Long as the Lemon Trees Grow: - Keisha Fitria Hendrawan; Fadlil Yani Ainusyamsi; Maman Abdul Djaliel (Raja Zulkarnain Education Foundation, 2026)
This study aims to examine the intertextual dialogue between Nizar Qabbani's poem Qabbani “تَرصيعٌ بِالذَّهَبِ عَلَى سَيْفٍ دِمَشْقِيٍّ” and Zoulfa Katouh's novel *As Long as the Lemon Trees Grow* in constructing meaningful relationships across genres and generations. This study is based on the theoretical view that literary works never exist in isolation, but rather are always in dialogue with other texts through intertwined symbols, themes, and values. The focus of the research is directed at how the meanings present in Qabbani's poem are reactualized and reconstructed in Katouh's novel through different social and historical contexts, particularly within the contemporary Syrian conflict landscape. This study uses a qualitative method with a descriptive-analytical approach. The data sources were obtained from two literary texts, namely a poem by Nizar Qabbani and a novel by Zoulfa Katouh. The analysis was conducted using the concept of intertextuality through intensive reading techniques (close reading) to explore the hypost and hypertextual relationships established between the two works. The results of the study indicate the presence of six main forms of intertextual dialogue, namely: (1) the symbol of the lemon as a metaphor for the continuity of life and hope, (2) the relationship between the ghazal and love for the homeland, (3) the concept of anîn as collective nostalgia that undergoes a transformation into trauma, (4) the representation of the house as a space of identity, (5) muqâwamah as a form of moral and humanitarian resistance. These findings indicate that Katouh's novel does not simply echo Qabbani's poem, but reconstructs its meaning according to the reality of the Syrian war, thus presenting a dynamic dialogue of meaning between two Arabic literary works from different historical contexts.